NATO- Türkiye İlişkileri: Vazgeçilmez Ortaktan Şüpheli Müttefike - BÖLME, SELİN MUZAFFER (My University, 2022)
With Russia’s invasion of Ukraine in late February 2022, Türkiye’s role in NATO has once again become a topic of intellectual discussion, with many observers arguing that a revival of Russian power would lead to Türkiye’s return to the alliance as a good-standing member, while others questioned the likelihood of such a scenario due to the country’s political transformation. This is not the fi rst time Türkiye’s role within the alliance has become a subject of debate. Türkiye is often described as a valuable and dedicated partner of NATO. Yet, since the beginning of its membership, the country’s role in the alliance has been questioned more than that of any other member state. This article seeks to analyse NATO’s relations with Türkiye and the country’s role within the alliance from a historical perspective. It aims to understand the debates on Türkiye’s role within NATO by focusing on the moments of transformation in relations. The main assumption of this article is that, from the beginning of Türkiye’s membership process, TurkishAmerican relations have been the main determinant of Türkiye-NATO relations. Türkiye’s role, defence, and identity have always been questioned by European members. But these debates on Türkiye had, until as recently as the 2010s, been directed and/or suppressed by the US in accordance with its own interests. The US had been the main supporter of Türkiye in the alliance against the opposition and criticism of Europeans in exchange for Türkiye’s commitment to US policies. While differences on interests and values between the US and Türkiye became more visible after 2010, Türkiye failed to secure the support of the alliance’s European members to fi ll the gap left by the waning US support. Indeed, the differences between them grew from security-based issues, to wider, more major identity issues.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Political Science; International Relations; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities; Turkey; Türkiye; NATO; United States; Transatlantic Security